Lightweight reputation-based approach against simple and cooperative black-hole attacks for MANET. (December 2018) - Hammamouche, Assia; Omar, Mawloud; Djebari, Nabil; Tari, Abdelkamel
Abstract: Ad hoc network is a set of mobile nodes interconnected by wireless communication. It is easily and less expensive to deploy, but it is vulnerable against various attacks. The node data should cross a set of intermediate nodes in order to reach the intended destination. An intermediate node, which takes part of the routing process, can behave maliciously and drop the packets passing through it instead of transferring them to its successor, which leads to what is called black hole attack. Several solutions have been proposed in the literature review. However, these solutions suffer from the imbalance between robustness and overhead. In this context, we propose a solution based on reputation of nodes and multi-hop acknowledgment. The reputation of nodes increases or decreases depending on the situation and the observation condition. When the node reputation passes below the threshold, then it will be considered as a black hole node. The proposed approach detects and excludes simple and cooperative black hole attackers and enforces the cooperation among the network nodes. Through simulation, we compare the proposed approach to a concurrent protocol and we show its efficiency in terms of detection ratio and communication overhead.